The Role of Prebiotics and Probiotics in Prevention of Allergic Diseases in Infants - Sestito, Simona; D'Auria, Enza; Baldassarre, Maria Elisabetta; Salvatore, Silvia; Tallarico, Valeria; Stefanelli, Ettore; Tarsitano, Flora; Concolino, Daniela; Pensabene, Licia (Frontiers in Pediatrics, 2020)
Allergic diseases have been linked to genetic and/or environmental factors, such as antibiotic use, westernized high fat and low fiber diet, which lead to early intestinal dysbiosis, and account for the rise in allergy prevalence, especially in western countries. Allergic diseases have shown reduced microbial diversity, including fewer lactobacilli and bifidobacteria, within the neonatal microbiota, before the onset of atopic diseases. Raised interest in microbiota manipulating strategies to restore the microbial balance for atopic disease prevention, through prebiotics, probiotics, or synbiotics supplementation, has been reported. We reviewed and discussed the role of prebiotics and/or probiotics supplementation for allergy prevention in infants. We searched PubMed and the Cochrane Database using keywords relating to “allergy” OR “allergic disorders”, “prevention” AND 'prebiotics' OR 'probiotics' OR ‘synbiotics’. We limited our evaluation to papers of English language including children aged 0-2years old. Different products or strains used, different period of intervention, duration of supplementation, has hampered the draw of definitive conclusions on the clinical impact of probiotics and/or prebiotics for prevention of allergic diseases in infants, except for atopic dermatitis in infants at high-risk. This preventive effect on eczema in high-risk infants is supported by clear evidence for probiotics but only moderate evidence for prebiotic supplementation. However, the optimal prebiotic or strain of probiotic, dose, duration, and timing of intervention remains uncertain. Particularly, a combined pre- and post-natal intervention appeared of stronger benefit, although the definition of the optimal intervention starting time during gestation, the timing, and duration in the postnatal period, as well as the best target population, are still an unmet need.